Health Education On Nutrition Pattern Management For Patients With Type 2 Diabetes Mellitus - Safwendra, Ewen; Dormina, Dormina; Martawinarti, RTS Netisa; Nurhusna, Nurhusna (Program Studi Keperawatan Universitas Jambi, 2025)
Diabetes Mellitus (DM) is a group of metabolic disorders characterized by chronic hyperglycemia due to defects in insulin secretion or insulin action. The global prevalence of DM continues to rise, with Type 2 Diabetes Mellitus (T2DM) being the most common form. Effective management of T2DM involves both pharmacological and non-pharmacological strategies, with nutritional therapy playing a pivotal role in maintaining blood glucose levels. Structured nutrition education has proven beneficial in enhancing dietary habits and improving glycemic control in T2DM patients. This study aimed to evaluate the impact of health education on nutritional restrictions in T2DM patients at the Pakuan Baru Public Health Center, Jambi City. The study employed a descriptive case study design, using a nursing care approach that included assessment, diagnosis, planning, implementation, and evaluation. A single participant, Mrs. Y, diagnosed with T2DM, was selected based on specific inclusion criteria. The study utilized a pre- and post-test questionnaire to measure the patient’s knowledge of nutritional restrictions. Before the intervention, Mrs. Y demonstrated limited knowledge of appropriate dietary practices for managing T2DM. Following a structured health education session, the patient’s knowledge significantly improved, as indicated by an increase in test scores from 46.6% to 80%. The findings suggest that personalized health education can effectively enhance patients’ understanding of dietary restrictions, leading to improved self-management of T2DM. This highlights the importance of incorporating health education into routine care for chronic conditions like diabetes. Future research should explore the long-term effects of such educational interventions and expand the sample size to further validate these findings.